Faktor-faktor yang Terkait Paparan Pestisida dan Hubungannya dengan Kejadian Anemia pada Petani Hortikultura di Desa Gombong Kecamatan Belik Kabupaten Pemalang Jawa Tengah - Siti Aisyah Kurniasih; Onny Setiani; Sri Achadi Nugraheni (Jurnal Kesehatan Lingkungan Indonesia, 2013)
Background : Agropolitan Gombong village is predominantly rural subsistence farmers have vegetables certainlywill not be free from the effects of pesticide poisoning that used to be abundant agricultural products. From thepreliminary study found 30% of farmers had hemoglobin levels below 12 gr% and the researchers found sometypical symptoms that farmers often complain of dizziness, weakness, if you get up from sitting dizzy eyes.Thepurpose of this study was to analyze the factors related to pesticide exposure and its relationship to the incidenceof anemia among horticultural farmers in the village of Pemalang Belik Kingpin District.Metods:This study was an analytic research with cross sectional approach. Data obtained through interviewedusing questionnaires and laboratory tests. The sampleswere 40 respondents. The results were analyzed usingchisquare test.Result : Using Binary Logistic Regression test showed exposure to pesticides have a tendency of 5,333 timesgreater effect on the incidence of anemia compared to respondents who were not exposed to pesticides.Conculsion : The government have to aggressively conduct outreach, for farmers to follow proper standards ofpesticide spraying and the public always wash vegetables consumed with running water and cooked food toreduce pesticide levels attached to the agricultural.Keywords : Pesticides, Exposure, Anemia